1999
DOI: 10.1097/00007632-199912010-00012
|View full text |Cite
|
Sign up to set email alerts
|

Personal Risk Factors for First-Time Low Back Pain

Abstract: Personal risk factors explained up to 12% of first-time low back pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
155
2
10

Year Published

2003
2003
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 261 publications
(181 citation statements)
references
References 64 publications
14
155
2
10
Order By: Relevance
“…These results were probably Independent variables entered together, discriminant coefficients C0.50 in italics Eur Spine J (2013) 22:1979-1985 1983 not affected by age-related side effects, although significance failed by 1.6 % for the comparison of controls and younger patients in a univariate analysis (Table 5). This result was in line with findings that revealed frontal plane asymmetries as risk factor for the development of low back pain [1,2]. In terms of our rasterstereography spinal form assessment, sagittal plane spine shape parameters could not be exposed clearly by multivariate factor analysis procedures as LBP indicating variables, but in discriminant analyses sagittal plane parameters were extracted as variables being able to separate controls from LBP patients of different age (Table 4).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These results were probably Independent variables entered together, discriminant coefficients C0.50 in italics Eur Spine J (2013) 22:1979-1985 1983 not affected by age-related side effects, although significance failed by 1.6 % for the comparison of controls and younger patients in a univariate analysis (Table 5). This result was in line with findings that revealed frontal plane asymmetries as risk factor for the development of low back pain [1,2]. In terms of our rasterstereography spinal form assessment, sagittal plane spine shape parameters could not be exposed clearly by multivariate factor analysis procedures as LBP indicating variables, but in discriminant analyses sagittal plane parameters were extracted as variables being able to separate controls from LBP patients of different age (Table 4).…”
Section: Discussionsupporting
confidence: 87%
“…Especially, frontal plane spinal asymmetries were identified to be a risk factor for low back pain syndromes [2]. When the most predictive factor for the development of low back pain-earlier back pain periods-could be controlled statistically, a flatter lumbar lordosis angle could be identified as a risk factor [1]; mathematical modeling studies reported a tendency for a flatter lordosis angle in chronic low back pain patients, too [11]. Some radiological findings in adults confirmed a flatter lumbar lordosis to be associated with chronic low back pain [13].…”
Section: Introductionmentioning
confidence: 99%
“…The search strategy identified 7,765 unique studies that were all screened based on title and abstract, and resulted in 81 potentially eligible studies. Sixty-two studies were excluded based on full-text screening and, therefore, 19 articles (reporting data from 16 studies) were included in the review (6)(7)(8)(9)(10)(11)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Two published articles (20,22) reported findings of the same study and were both included in the review, as they provided results for different time points.…”
Section: Resultsmentioning
confidence: 99%
“…The samples were recruited from the general population in 13 articles (6)(7)(8)19,21,(23)(24)(25)(26)(27)(28)(29)(30) and from a workplace in 6 articles (9)(10)(11)18,20,22). The assessment of symptoms of depression varied across the studies, but overall they could be categorized into 3 groups: diagnostic interview, self-report screening questionnaires, and nonspecific screening questionnaires (questionnaires that assessed more general categories of psychological distress, including but not limited to, symptoms of depression).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation